Volatility and spillover effects of oil and food price shocks-application of time series econometrics - Fardous, Alom (LAP Lambert Academic Publishing Co. Ltd, 2012)
The skyrocketing prices of oil and food are matters of great concerns for consumers, producers, national and international bodies. This book addresses this aspect in five independent but related essays. The first two essays model the extent of volatility of oil and food price shocks. Third essay examines the cross country mean and volatility spillover effects of food prices while the fourth essay investigates the spillover effects of oil prices on the food prices of selected Asia and Pacific countries. Finally, the fifth essay assesses the economic impacts of oil and food prices in the context of selected Asia and Pacific countries. Overall, the findings show that both oil and food prices have persistence effects on the volatility while the evidence of asymmetry is mixed; there is considerable cross country mean and volatility spillover effects of food prices; oil prices positively spillover to food prices and the impacts of oil and food prices to macroeconomic variables are dependent on the economic characteristics of individual economies.